2016
DOI: 10.1002/pbc.26231
|View full text |Cite
|
Sign up to set email alerts
|

A randomized nutrition counseling intervention in pediatric leukemia patients receiving steroids results in reduced caloric intake

Abstract: A year-long dietary intervention was effective at reducing caloric intake in pediatric ALL patients receiving steroid-based chemotherapy, indicating that this is a modality that can be built upon for obesity prevention and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 24 publications
0
51
0
2
Order By: Relevance
“…Dietary and exercise‐based interventions are being developed for children with cancer with greater frequency. For example, recent randomized controlled trials have demonstrated the effectiveness of dietary and physical activity interventions in reducing caloric intake in patients with acute lymphoblastic leukemia receiving steroids or increasing physical activity and weight loss in survivors . Integrating interventions within the transtheoretical model may heighten the chance of success of these interventions and allows for a theoretical framework with which to guide investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary and exercise‐based interventions are being developed for children with cancer with greater frequency. For example, recent randomized controlled trials have demonstrated the effectiveness of dietary and physical activity interventions in reducing caloric intake in patients with acute lymphoblastic leukemia receiving steroids or increasing physical activity and weight loss in survivors . Integrating interventions within the transtheoretical model may heighten the chance of success of these interventions and allows for a theoretical framework with which to guide investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One full‐text was excluded as the study participants with chronic conditions were not using corticosteroids, leaving three included studies that were published between 2009 and 2017. These mainly reported on work undertaken in Anglo‐American contexts (the United Kingdom and United States).…”
Section: Resultsmentioning
confidence: 99%
“…All included studies used experimental designs (Table ). Each study had a small sample size, ranging from 13 patients to 23 patients . The studies differed in terms of length of observation and population included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations